THE ECONOMIC ESSENCE AND SPECIFIC FEATURES OF TOURISM SERVICES EXPORT - Hamrayev Umidbek Murodjon ugli (International Journal of Literature and Language Studies, 2026)
Abstract. This article provides a scientific analysis of the economic essence of tourism services export, its role in the national economy, its specific features within the system of trade in services, and the modern factors shaping its development. The study substantiates that tourism services export, as an important segment of foreign economic activity, has the potential to increase foreign currency earnings, expand employment, stimulate regional development, and generate a multiplier economic effect. The article highlights the distinctive features of tourism export compared with commodity export, including its intangible nature, the simultaneous occurrence of production and consumption, dependence on infrastructure, and close relationship with institutional governance. In addition, contemporary trends in the international tourism market are examined, including digitalization, sustainability, diversification of services, and the formation of tourism products with high added value. The study concludes by formulating scientific and practical recommendations on the priority directions for developing tourism services export.